On the Six Years of the Operation and Regulating of EMU - Rácz, MARGIT (Papeles del Este, 2006)
The separation of the two elements of financial policy, the parting of fiscal and monetary policies in the decision-making system is one of the most unique features of the Economic and Monetary Union (EMU). Concerning fiscal policy, the Treaty of Maastricht and the Stability and Growth Pact (SGP) only contain equilibrium requirements. It is evident since 2002 that meeting the requirements of SGP has proved unachievable for a number of member-countries. Consequently, the most important challenge the Economic and Monetary Union faces these days is whether stability can be secured without strict fiscal regulations.